Nerve damage induced skeletal muscle atrophy is associated with increased accumulation of intramuscular glucose and polyol pathway intermediates - Langer, Henning Tim (Sci Rep, 2020)
Perturbations in skeletal muscle metabolism have been reported for a variety of neuromuscular diseases. However, the role of metabolism after constriction injury to a nerve and the associated muscle atrophy is unclear. We have analyzed rat tibialis anterior (TA) four weeks after unilateral constriction injury to the sciatic nerve (DMG) and in the contralateral control leg (CTRL) (n = 7) to investigate changes of the metabolome, immunohistochemistry and protein levels. Untargeted metabolomics identified 79 polar metabolites, 27 of which were significantly altered in DMG compared to CTRL. Glucose concentrations were increased 2.6-fold in DMG, while glucose 6-phosphate (G6-P) was unchanged. Intermediates of the polyol pathway were increased in DMG, particularly fructose (1.7-fold). GLUT4 localization was scattered as opposed to clearly at the sarcolemma. Despite the altered localization, we found GLUT4 protein levels to be increased 7.8-fold while GLUT1 was decreased 1.7-fold in nerve damaged TA. PFK1 and GS levels were both decreased 2.1-fold, indicating an inability of glycolysis and glycogen synthesis to process glucose at sufficient rates. In conclusion, chronic nerve constriction causes increased GLUT4 levels in conjunction with decreased glycolytic activity and glycogen storage in skeletal muscle, resulting in accumulation of intramuscular glucose and polyol pathway intermediates.